2022
DOI: 10.1002/ente.202200437
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Current Impedance Probing Capacity of Lithium‐Ion Battery by Gaussian Process Regression

Abstract: Alternating current (AC) impedance is an important and promising feature for lithium‐ion battery state estimation and prediction. Herein, a new battery capacity estimation method using AC impedance with Gaussian process regression (GPR) is proposed. A bunch of high‐energy 18 650‐type batteries with a nominal capacity of 3.5 Ah are cycled at 25, 35, and 45 °C until the capacity drops below 2.6 Ah. Two single‐frequency points are found which are highly correlated with the battery residual capacity regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Locorotondo et al found that there may be a certain frequency point that can be considered as a reliable indicator of SOH through data clustering . Zhu et al first investigated the relations between battery capacity and impedance, which found that the impedance at two frequencies (0.25 and 398 Hz) exhibited the highest correlation coefficient with the capacity fade . Therefore, they used the real and imaginary part of the two single-frequency impedance, i.e., four parameters, as features combined with different machine learning algorithms, including linear regression (LR), support vector machine (SVM), and Gaussian process regression (GPR).…”
Section: Application Of Eis To Lib’s Aging Studymentioning
confidence: 99%
“…Locorotondo et al found that there may be a certain frequency point that can be considered as a reliable indicator of SOH through data clustering . Zhu et al first investigated the relations between battery capacity and impedance, which found that the impedance at two frequencies (0.25 and 398 Hz) exhibited the highest correlation coefficient with the capacity fade . Therefore, they used the real and imaginary part of the two single-frequency impedance, i.e., four parameters, as features combined with different machine learning algorithms, including linear regression (LR), support vector machine (SVM), and Gaussian process regression (GPR).…”
Section: Application Of Eis To Lib’s Aging Studymentioning
confidence: 99%
“…The introduction of machine learning methods can effectively overcome these limitations and provide a faster, efficient and accurate optimization strategy. [ 208,209 ]…”
Section: Application Of Machine Learning Methods In Licoo2 Cathodementioning
confidence: 99%
“…The introduction of machine learning methods can effectively overcome these limitations and provide a faster, efficient and accurate optimization strategy. [208,209] First of all, machine learning methods can quickly screen out LiCoO 2 cathode materials with potentially excellent performance by establishing a correlation model between material structure and performance. With a large amount of experimental data and computational results, highly accurate predictive models can be trained to provide targeted guidance in material design.…”
Section: Future Strategies Of Machine Learning Methods In Optimizing ...mentioning
confidence: 99%